Transformative Social-Emotional Learning for Teachers: Critical and Holistic Well-Being as a Marker of Success - Soutter, Madora (Journal of Teaching and Learning, 2023)
Social and emotional learning (SEL) is a crucial part of student wellness and academic achievement, but teachers’ own SEL is often overlooked. This qualitative study examines educators’ perceptions of their own university-level teacher preparation programs to better understand the ways in which teacher educators can support pre-service teachers’ well-being, preparedness, and longevity in the field. Findings reveal that teachers saw their own transformative SEL—a form of SEL committed to equity and social justice (Jagers et al., 2019)—as a key factor for their success, highlighting the importance of critical and holistic preparation that focuses on the social–emotional development of teachers themselves. Implications focus on practical ways transformative SEL can be infused into teacher preparation programs including redefining success beyond student academics alone, focusing on teacher well-being in a way that does not ignore systemic oppression and school-level barriers, preparing teachers for the realities of roadblocks and ethical dilemmas they may face, and examining syllabi and coursework for the development of transformative SEL competencies.